Antecedents of Green Purchase Intention using the Theory of Planned Behavior Model: Evidence from India - Surender Badavath; KVLN Pavan Kumar; Swathi Mathur; Rambabu Lavuri (Indonesian Journal of Sustainability Accounting and Management, 2024)
The study’s purpose is to examine the effect of antecedents (green ads, green brand image, environmental knowledge, concern, and attitude) on green purchase intention using the theories of reasoned action and planned behavior, with subjective norms and perceived behavioral control acting as moderators. Snowball sampling was used to collect data from 323 Indian respondents, which was then analyzed using structural equation modelling. The findings show that green ads and brand image significantly impacted environmental knowledge, concern, and attitude. Similarly, environmental knowledge had a positive impact on environmental concern and green attitude but did not impact green purchase intention, whereas environmental concern had a favorable impact on green attitude but did not impact green purchase intention; attitude had a significant impact on green purchase intention. Moderation results revealed that subjective norms had a positive moderation relationship between attitude and green purchase intention. However, there was no moderate relationship between environmental knowledge, concern, and green purchase intention. In contrast, perceived behavioral control had a positive moderation relationship between environmental knowledge, concern, attitude, and green purchase intention.